Judicial Texture and Symbolic Mediations in Volverás a Región, by Juan Benet (XXI Century. Spanish Literature and Culture, 2004)
The diversity of interests amongst readers and scholars of the subjects dealt with in Volverás aRegión accentuates de lack of connection that said novel has with judicial discourse. For this, twointertwined perspectives are taken: the permeability of the narrative, which enriches the discoursiveregisters of the novel; and instances of the abandoned child that is its main character, such as affectivelaws and custom law – which presents a sort of incursion into the judicial field.
Keywords: Benet; Volverás a Región; analysis; judicial discourse; laws